Hepatocellular Carcinoma in Non-Alcoholic Fatty Liver Disease: From Epidemiology to Diagnostic Approach - Ivica Grgurevic (MDPI AG, 2021)
Non-alcoholic fatty liver disease (NAFLD) is becoming the leading cause of liver morbidity worldwide and, as such, represents the pathogenic background for the increasing incidence of hepatocellular carcinoma (HCC). The annual incidence of NAFLD-related HCC is expected to increase by 45–130% by 2030. Diabetes mellitus is the most important risk factor for HCC development in NAFLD, with the risk further increased when associated with other metabolic traits, such as obesity, arterial hypertension and dyslipidemia. The highest risk of HCC exists in patients with advanced fibrosis or cirrhosis, although 20–50% of HCC cases arise in NAFLD patients with an absence of cirrhosis. This calls for further investigation of the pathogenic mechanisms that are involved in hepatocarcinogenesis, including genetics, metabolomics, the influence of the gut microbiota and immunological responses. Early identification of patients with or at risk of NAFLD is of utmost importance to improve outcomes. As NAFLD is highly prevalent in the community, the identification of cases should rely upon simple demographic and clinical characteristics. Once identified, these patients should then be evaluated for the presence of advanced fibrosis or cirrhosis and subsequently enter HCC surveillance programs if appropriate. A significant problem is the early recognition of non-cirrhotic NAFLD patients who will develop HCC, where new biomarkers and scores are potential solutions to tackle this issue.